Analytical Causative Construction in Banyumasan Dialect and West Kalimantan Hakka Dialect: A Linguistic Typology Study - Julius Novan Deni Kurniawan; Agus Subiyanto (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
This study was conducted to compare the similarities and differences that exist in the analytic causative construction in the languages of the Austronesian family represented by the Banyuman Dialect (BD) and the Sino-Tibetan family represented by the West Kalimantan Hakka Dialect (WKHD). This descriptive qualitative research uses the analytical causative theory from Comrie (1989), which aims to analyze the analytic causative construction in BD and WKHD. The results show differences in the number of analytic causative verbs with equivalent meanings in the two languages. Furthermore, there are similarities in analytic causative productivity in both languages. Finally, there are differences in sentence construction between the two languages.